Water Quality Monitoring System Using IOT - Pokhrel, Suruchi; Pant, Anisha; Gautam, Ritisha; Kshatri, Dinesh Baniya (Journal of Innovations in Engineering Education, 2020)
Water pollution is one of the growing issues in a developing country like Nepal. In the present scenario, we are usually thoughtlessly trusting the drinking water suppliers with our health. Even though the water is purified as well as checked in the central distribution systems, the supplier, along with the general public is unaware of the water quality that reaches the end-users. By focusing on these above issues, we propose a low-cost monitoring system that can monitor water quality such as pH (potential of Hydrogen) and conductivity on a timely basis using the Internet of Things. The water quality monitoring sensors sense the necessary physical parameters and convert them into equivalent electrical form, i.e. by providing certain voltage as an output corresponding to the respective physical quantity. This value is mapped to the respective water quality measure and is stored in a database through the microcontroller using the Internet of Things. This aids the suppliers to centralize the regular monitoring of water from various locations as well as the supply pure water to the end-users.